Composite pigment, thermoplastic resin composition containing the same, and molded article
By using a porous pigment layer in the composite pigment, combining pigment, resin and metal oxide, the problems of insufficient water resistance and pigment peeling of the existing composite pigment are solved, and a molded body with high color and color uniformity is achieved.
Patent Information
- Application Number
- CN202180045579.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-02
- Filing Date
- 2021-06-21
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-06-21
AI Technical Summary
The existing composite pigments are insufficiently water-resistant when used in aqueous coatings and are easily dissolved. When mixed with thermoplastic resin at high temperatures, the pigments may be peeled off from the substrate particles, resulting in a decrease in the color of the molded body and uneven color tone.
A composite pigment is used, which includes substrate particles and a porous pigment layer on the surface of substrate particles. The pigment layer is composed of pigments, resins and metal oxides. The resin is a three-dimensional crosslinked structure. The metal oxide includes silicon oxides, polysiloxanes and their composites to improve the water resistance and mechanical strength of the pigment layer.
The water resistance of the composite pigment is significantly improved, and the peeling of the pigment when kneading with the thermoplastic resin at high temperature is suppressed, so as to maintain the high color and color uniformity of the molded body.
Smart Images

Figure CN115996993B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite pigment, a thermoplastic resin composition containing the composite pigment, and a molded body. Background Art
[0002] As a method of imparting an appearance having both brilliance and high chroma, there is a composite pigment in which the surface of brilliance base particles is coated with a color pigment.
[0003] For example, Patent Document 1 (WO 2014 / 050893) discloses a composite pigment (colored aluminum pigment) in which a colored pigment is attached to the surface of flaky aluminum particles.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: WO2014 / 050893 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, water resistance is insufficient, so when used for water-based paints, the use of pigments that are easily dissolved into aqueous solvents is limited, especially when the substrate is metal, if the water-based paint is stored in a heated state, there is a problem of generating hydrogen due to corrosion of the metal. In addition, when using the composition obtained by incorporating the above-mentioned composite pigment into a thermoplastic resin to manufacture a molded body, since the composite pigment and the thermoplastic resin are mixed at high temperature, the pigment (coloring pigment) is likely to be peeled off from the substrate particles and freed in the thermoplastic resin. Therefore, there is also a problem of reduced chroma or uneven color tone of the obtained molded body.
[0009] Therefore, an object of the present invention is to provide a composite pigment which is excellent in water resistance and in which separation of the pigment from substrate particles is suppressed.
[0010] Means for solving problems
[0011] [1] A composite pigment comprising a substrate particle and a pigment layer provided on a surface of the substrate particle.
[0012] The pigment layer contains pigment, resin and metal oxide.
[0013] The metal oxide includes at least one selected from silicon oxide, polysiloxane, and a composite thereof.
[0014] [2] The composite pigment according to [1], wherein the resin is a radical polymer of at least one of a monomer and an oligomer, and at least one of the monomer and the oligomer has two or more polymerizable double bonds.
[0015] [3] The composite pigment according to [1] or [2], wherein the substrate particles contain at least one selected from the group consisting of aluminum, aluminum alloys, glass, alumina, and mica.
[0016] [4] The composite pigment according to any one of [1] to [3], wherein the pigment layer is porous.
[0017] [5] The composite pigment according to [4], wherein the specific surface area of the pigment layer is 10 to 100 m 2 / g.
[0018] [6] A thermoplastic resin composition comprising the composite pigment described in any one of [1] to [5].
[0019] [7] A molded article comprising the thermoplastic resin composition described in [6].
[0020] Effects of the Invention
[0021] The composite pigment of the present invention has more excellent water resistance than conventional composite pigments to which a coloring pigment is attached.
[0022] In addition, the pigment is fixed on the surface of the substrate particles by resin, and the resin is further given heat resistance and mechanical strength by metal oxide, thereby suppressing the peeling (falling off) of the pigment from the substrate particles during kneading at high temperature, etc. Therefore, according to the present invention, a thermoplastic resin composition can be provided, which contains a composite pigment in which the peeling of the pigment from the substrate particles is suppressed when the composite pigment is used in the manufacture of a molded body, etc.
[0023] This can suppress a decrease in chroma, unevenness in color tone, and the like of a molded product obtained using the composite pigment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic cross-sectional view showing a composite pigment according to an embodiment.
[0025] Figure 2 It is a schematic diagram showing an enlarged cross section of an example of the composite pigment according to the embodiment.
[0026] Figure 3 (a) is an optical microscope photograph of the surface of a molded body obtained using the composite pigment of Example 1. Figure 3 (b) is an optical microscope photograph of the surface of a molded body obtained using the composite pigment of Comparative Example 1.
[0027] Figure 4 (a) is a SEM photograph (reference photograph) showing a cross section of an example of the composite pigment according to the embodiment. Figure 4 (b) is a SEM photograph showing a cross section of an example of a composite pigment different from that of the embodiment (comparative reference photograph).
[0028] Figure 5 (a) is a BF-STEM image showing a cross section near the surface of the composite pigment of Example 1. Figure 5 (b) is a HAADF-STEM image showing a cross section near the surface of the composite pigment of Example 1.
[0029] Figure 6 yes Figure 5 A local magnified image of area (I).
[0030] Figure 7 yes Figure 6 A local magnified image of area (II).
[0031] Figure 8 yes Figure 7 A local magnified image of .
[0032] Fig. 9 yes Figure 6 A local magnified image of area (III).
[0033] Fig.10 yes Fig. 9 A local magnified image of .
[0034] Fig.11 (a) is related to Figure 7 (b) HAADF-STEM image of almost the same field of view. Fig.11 (b)~(h) are related to Figure 7 STEM-EDX images of almost the same field of view. Figure 11 to Figure 13 and Fig.16 (b) to (h) are images showing the distribution of C, N, O, Al, Si, Cl, and Cu, respectively.)
[0035] Fig.12 (a) is related to Figure 8 (b) Same image. Fig.12 (b)~(h) are related to Figure 8 STEM-EDX image of the same field of view.
[0036] Fig.13 (a) is related to Fig.10 (b) Same image. Fig.13 (b)~(h) are related to Fig.10STEM-EDX image of the same field of view.
[0037] Fig.14 yes Figure 6 A local magnified image of area (IV).
[0038] Fig.15 yes Fig.14 A local magnified image of .
[0039] Fig.16 (a) is related to Fig.15 (b) Same image. Fig.16 (b)~(h) are related to Fig.15 STEM-EDX image of the same field of view. DETAILED DESCRIPTION
[0040] <Compound Pigments>
[0041] Reference Figure 1 In the composite pigment of the present embodiment, the composite pigment 1 includes a substrate particle 2 and a pigment layer 3 provided on the surface of the substrate particle 2 .
[0042] The pigment layer 3 contains a pigment, a resin, and a metal oxide. The metal oxide includes at least one selected from silicon oxide, polysiloxane, and a composite thereof.
[0043] More specifically, for example Figure 2 As shown, on the surface of the substrate particle 2, the pigment layer 3 is composed of a plurality of particles in which a pigment 3a is coated with a resin 3b, and a metal oxide (not shown) is attached to the surface 3c of the plurality of particles.
[0044] That is, in the present embodiment, in the pigment layer 3 including the pigment, the resin, and the metal oxide, the composite of the resin and the metal oxide exists in a state of being interposed between the plurality of pigments.
[0045] The resin 3b contained in the pigment layer 3 has a three-dimensional cross-linked structure, so it is not easy to melt even if heated. In addition, the metal oxide present in the pigment layer 3 (for example, on the surface of the resin 3b) together with the resin 3b improves water resistance. In addition, the mechanical strength is also improved, so when the composite pigment is added to the resin and kneaded, or when it is added to the paint and stirred, it is also possible to suppress the peeling (falling off) of the pigment from the surface of the substrate particles.
[0046] On the other hand, Figure 4In the composite pigment 1 shown in the comparative reference photograph (b) (SEM (scanning electron microscope) image after osmium staining), a layer 30 consisting only of pigment is formed near the surface of the substrate particle 2, and a layer 31 containing metal oxide and resin is formed on the surface of the layer 30. In this way, the resin and the metal oxide are located outside the pigment, so the layer 30 consisting only of pigment becomes brittle. Therefore, when the thermoplastic resin and the composite pigment are kneaded at high temperature, the pigment is peeled off from the substrate particle and released into the thermoplastic resin. It should be noted that Figure 4 The photograph of FIG. 4 is a photograph of a composite pigment 1 present in a thermoplastic resin 4 .
[0047] In contrast, Figure 4 As shown in the reference photograph (a), in the composite pigment 1 of this embodiment, a pigment layer 3 in which a pigment, a resin and a metal oxide are mixed is formed on the surface of the substrate particle 2. Thus, the pigment layer itself, which is endowed with water resistance, can be made the outermost layer, and a composite pigment having high water resistance and maintaining chroma can be obtained.
[0048] In addition, when the thermoplastic resin and the composite pigment are kneaded at high temperature, the peeling of the pigment from the base particles can be suppressed, thereby suppressing the reduction in chroma and unevenness in color tone of the molded body obtained using the composite pigment.
[0049] 〔Base material particles〕
[0050] The substrate particles are particles that serve as a base material for the composite pigment. The substrate particles preferably have glitter at least on their surface.
[0051] Examples of the substrate particles having glitter include metal flakes of aluminum, titanium, copper, brass, stainless steel, and the like. In addition, examples thereof include natural mica, synthetic mica, alumina flakes, and glass flakes.
[0052] The present invention is particularly effective when the substrate particles are made of aluminum or an aluminum alloy which is prone to the problem of gas generation.
[0053] In addition, as the substrate particles, particles subjected to water resistance treatment using a phosphorus compound, a molybdenum compound, or the like, or particles coated with a resin, a metal oxide, or the like may be used.
[0054] The shape of the substrate particles is not particularly limited, and for example, a flake shape, a scale shape, a disk shape, an elliptical disk shape, etc. are particularly preferred.
[0055] The size of the substrate particles is not particularly limited, and for example, particles having a D50 of 1 μm to 200 μm in volume distribution by laser diffraction can be preferably used.
[0056] 〔Pigment layer〕
[0057] The pigment layer is provided on the surface of the substrate particles. The pigment (coloring pigment) may be directly fixed to the surface of the substrate particles or may be indirectly fixed to the substrate particles via an adhesive component such as a resin.
[0058] The pigment layer contains pigment, resin and metal oxide.
[0059] Reference Figure 2 The pigment layer 3 is preferably composed of a matrix (three-dimensional cross-linked structure) containing particles of a resin 3b containing a pigment 3a and a metal oxide attached to its surface 3c.
[0060] (pigment)
[0061] As the pigment, various known pigments that exhibit a color tone can be used. The color tone is not particularly limited, and may be any of colored (color), white, black, etc., and may be opaque, translucent, or transparent.
[0062] As pigment, there is no particular limitation, for example, organic pigments such as pyrrolopyrrole diketo, quinacridone, dioxazine, isoindolinone, condensed azo, reduction, perinone, perylene, quinophthalone, phthalocyanine, and inorganic pigments such as iron oxide, titanium oxide, and carbon black can be cited. It should be noted that the pigment in this embodiment is a compound different from the metal oxide described later.
[0063] Specific examples of organic pigments include phthalocyanine, halogenated phthalocyanine, quinacridone, dione pyrrolopyrrole, isoindolinone, azomethine metal complexes, indanthrone, perylene, perinone, anthraquinone, dioxazine, benzimidazolone, condensed azo, triphenylmethane, quinophthalone, anthraquinone pyrimidine, and nigrosine.
[0064] Specific examples of the inorganic pigment include iron oxide, ultramarine, Prussian blue, cobalt blue, chrome green, bismuth vanadate, composite oxide calcined pigments, carbon black, titanium black, titanium oxide, and ultrafine titanium oxide.
[0065] The stacking amount of the pigment layer is preferably appropriately adjusted according to the specific surface area of the substrate particles. The average thickness of the pigment layer on one side of the substrate particle surface is preferably 1nm to 5μm. When the average thickness of the pigment layer is less than 1nm, the composite pigment may not be colored to a degree that fully reflects the design. In addition, when the average thickness of the pigment layer exceeds 5μm, the pigment layer is easy to peel off, or there is a tendency for the hiding power of the composite pigment per unit mass to decrease. It should be noted that the average thickness of the pigment layer can be measured by exposing the cross section by ion milling in a state embedded in the resin and using an electron microscope.
[0066] It should be noted that even a coloring material generally classified as a dye can be used as a pigment in the present embodiment as long as it is a coloring material that maintains a particle state under predetermined conditions.
[0067] (resin)
[0068] As resin, it is not particularly limited, and it is preferably a free radical polymer of at least any one of a monomer and an oligomer. At least one of the monomer and the oligomer preferably has more than two polymerizable double bonds. In this case, a three-dimensionally cross-linked resin (resin matrix) is efficiently formed, which is advantageous in terms of improving heat resistance.
[0069] In addition, the composition of the resin and the like will be described in detail in the “Method for Producing a Composite Pigment” described later.
[0070] The amount of the resin is not particularly limited, but is preferably an amount that can suppress the peeling of the pigment layer from the substrate particles and that the pigment layer is composed of a porous matrix. Specifically, the amount of the resin is preferably 5 to 100% by mass, more preferably 10 to 70% by mass, relative to the total amount of the pigment and the binder.
[0071] It should be noted that in the pigment layer, when the resin forms a porous matrix, the metal oxide can be attached to the surface containing the voids, so that the heat resistance and mechanical strength of the pigment layer can be effectively improved by the metal oxide. Therefore, the pigment layer is preferably porous. The specific surface area of the pigment layer is preferably 10 to 100 m 2 / g, more preferably 15 to 90 m 2 / g.
[0072] However, since water resistance, heat resistance and mechanical strength are insufficient if it is only a resin, in the composite pigment of the present embodiment, the pigment layer further contains a metal oxide.
[0073] (Metal Oxide)
[0074] The metal oxide is mixed with the pigment and the resin in the pigment layer. The metal oxide has heat resistance and mechanical strength, so even if it is heated and kneaded during molding, it can protect the pigment layer from the thermal deformation and mechanical stress of the protective layer and keep the pigment layer on the surface of the substrate. That is, the metal oxide has the effect of preventing the pigment layer from peeling off from the substrate and being released into the thermoplastic resin.
[0075] In this embodiment, the metal oxide comprises at least one selected from silicon oxide, polysiloxane and their composites. In order not to hinder the color development brought by the pigment, the metal oxide is preferably colorless. Silicon oxide, polysiloxane and their composites are excellent in terms of transparency, safety and production cost.
[0076] It should be noted that the metal oxide may also include components other than silicon oxide, polysiloxane and their composites. In this case, the constituent material of the metal oxide is not particularly limited, and an oxide or hydroxide of at least one element selected from Al, Si, Ti, Cr, Zr, Mo and Ce is preferably used. It should be noted that the metal oxide may also include hydrated water within the scope of not damaging the effect of the present embodiment.
[0077] It should be noted that silicon oxide and a composite (condensate) of silicon oxide and polysiloxane are oxides of Si. In addition, "polysiloxane" means a compound obtained by condensing an organic silicon compound through a siloxane bond.
[0078] The metal oxide is preferably amorphous because, if it is crystalline, it is hard but brittle and may break in applications where mechanical stress is applied, and water resistance and the like may be reduced.
[0079] <Method for producing composite pigment>
[0080] Hereinafter, one aspect of the method for producing the composite pigment according to the present embodiment will be described.
[0081] One aspect of the method for producing a composite pigment according to the present embodiment mainly includes the following pigment adhering step and pigment layer forming step.
[0082] (Pigment adhesion process)
[0083] The pigment attachment step is a step of attaching the pigment to the surfaces of a plurality of substrate particles. It should be noted that the pigment (coloring pigment) may be directly attached to the surfaces of the substrate particles or may be indirectly attached to the substrate particles via an adhesive component such as a resin.
[0084] As a method for attaching pigment to the surface of substrate particles, it is not particularly limited, and various known methods can be used. Specifically, for example, by adding carboxylic acid and / or amine compounds as a binder in substrate particles and pigment (coloring pigment) and mixing, the pigment can be attached to the surface of substrate particles. The binder is preferably a mixture of carboxylic acid and amine compounds. The carboxylic acid preferably has more than 2 carboxyl groups. The amine compound preferably has more than 2 amino groups. The amount of such a binder depends on the type and particle size of the pigment, but in order to make the pigment layer porous, the pigment per 100 mass parts is preferably less than 50 mass parts, more preferably less than 40 mass parts.
[0085] The ratio of the amount of the pigment to the total amount of the composite pigment is preferably 10 to 60% by mass, and more preferably 15 to 50% by mass. In this case, there are gaps between the pigments attached to the surface of the substrate particles, and the resin and the metal oxide enter the gaps, so that a pigment layer composed of the pigment, the resin and the metal oxide is easily formed.
[0086] (Pigment layer forming step)
[0087] In the pigment layer forming step, a pigment layer containing a pigment, a resin, and a metal oxide is formed. For example, a pigment layer containing a pigment attached to the surface of substrate particles, a metal oxide, and a resin having a three-dimensional crosslinked structure is formed.
[0088] As a method for forming the pigment layer, for example, the following method can be preferably adopted.
[0089] First, the pigmented substrate particles obtained in the coloring step are dispersed in a hydrocarbon solvent or an alcohol solvent (preferably a hydrocarbon solvent). Next, monomers and / or oligomers and a free radical polymerization initiator are added to the obtained slurry, and the mixture is heated while stirring to perform free radical polymerization, thereby precipitating a resin on the surface of the pigmented substrate particles.
[0090] Examples of the radical polymerization initiator include benzoyl peroxide, isobutyl peroxide, azobisisobutyronitrile, azobisisovaleronitrile, etc. The amount of the radical polymerization initiator added is preferably 1 part by mass or more and 50 parts by mass or less relative to 100 parts by mass of the monomer and / or oligomer.
[0091] The polymerization reaction is preferably carried out in an oxygen-free atmosphere (eg, an inert gas atmosphere such as nitrogen or argon). The polymerization reaction temperature is preferably 50 to 150° C., more preferably 70 to 110° C. The polymerization reaction time is preferably 30 minutes to 30 hours.
[0092] The monomers and oligomers are not particularly limited, and examples thereof include acrylic acid, methacrylic acid, methyl methacrylate, butyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, stearyl acrylate, cyclohexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxybutyl acrylate, 2-methoxyethyl acrylate, 2-diethylaminoethyl acrylate, butyl methacrylate, octyl methacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, neopentyl glycol diacrylate, tripropylene glycol diacrylate, and tetraethylene glycol diacrylate. , trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, tetramethylolmethane tetraacrylate, pentaerythritol triacrylate, triacryloxyethyl phosphate, ditrimethylolpropane tetraacrylate, styrene, α-methylstyrene, vinyltoluene, divinylbenzene, acrylonitrile, methacrylonitrile, vinyl acetate, vinyl propionate, maleic acid, crotonic acid, itaconic acid, polybutadiene, linseed oil, soybean oil, epoxidized soybean oil, epoxidized polybutadiene, cyclohexene vinyl monoxide, divinylbenzene monoxide, acid phosphate mono (2-acryloxyethyl) ester, acid phosphate mono (2-methyl 2-Acryloyloxyethyl) ester, 2-acryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, (2-hydroxyethyl) methacrylate acid phosphate, 2-methacryloyloxyethyl acid phosphate, 2-acryloyloxyethyl acid phosphate, diphenyl-2-methacryloyloxyethyl acid phosphate, diphenyl-2-acryloyloxyethyl acid phosphate, dibutyl-2-methacryloyloxyethyl acid phosphate, dibutyl-2-acryloyloxyethyl acid phosphate, dioctyl-2-methacryloyloxyethyl acid phosphate, dioctyl-2-acryloyloxyethyl acid phosphate, 2-Methacryloyloxypropyl phosphate, bis(2-chloroethyl)vinyl phosphonate, di-2-methacryloyloxyethyl acid phosphate, tri-2-methacryloyloxyethyl acid phosphate, di-2-acryloyloxyethyl acid phosphate, tri-2-acryloyloxyethyl acid phosphate, diallyl dibutyl phosphonate succinate, acrylic acid-modified polyester (degree of polymerization of about 2 to 20), acrylic acid-modified polyether (degree of polymerization of about 2 to 20), acrylic acid-modified urethane (degree of polymerization of about 2 to 20), acrylic acid-modified epoxy (degree of polymerization of about 2 to 20), acrylic acid-modified spirane (degree of polymerization of about 2 to 20), etc.
[0093] It is preferred that at least one of the monomer and the oligomer has two or more polymerizable double bonds. In this case, a three-dimensionally cross-linked resin (resin matrix) is efficiently formed, which is advantageous in terms of improving heat resistance.
[0094] When an organic silicon compound having a polymerizable double bond such as vinyltriethoxysilane, acryloxypropyltriethoxysilane, or methacryloxypropyltriethoxysilane is used as a monomer and / or oligomer, the resin and the metal oxide described below are strongly bonded to improve heat resistance.
[0095] It should be noted that the steps up to the step of coating with such a resin are the same as the method disclosed in International Publication No. 2014 / 050893.
[0096] Next, the substrate particles coated with the resin matrix containing the pigment are dispersed in a solvent. The solvent is not particularly specified, as long as it does not hinder the precipitation of the metal oxide based on the sol-gel method. For example, alcohol, glycol ether, hydrocarbon solvents, etc. can be cited. A metal compound and water that become the raw materials of the metal oxide are added to the obtained slurry, and an acid or a base is used as a catalyst to hydrolyze the metal oxide to precipitate. Thus, a pigment layer composed of the resin containing the pigment and the metal oxide is formed.
[0097] It should be noted that metal oxides such as Figure 2 As shown, it is preferably fixed to the surface 3c of the matrix containing particles of the resin 3b containing the pigment 3a. In order to easily obtain such a state, the amount of the metal compound is preferably 2.0 to 45.0% by mass (as solid content after TEOS reaction) relative to the total amount of the pigment and the binder, and more preferably 3.0 to 35.0% by mass (as solid content after TEOS reaction).
[0098] As the raw material of the metal oxide, known metal compounds that can be hydrolyzed can be used without particular limitation. As such metal compounds, for example, alkoxides, chlorides, carboxylates and acetylacetone complexes of Al, Si, Ti, Cr, Zr, Mo and Ce can be cited. As a specific example of the metal compound, for example, tetraethoxysilane (TEOS) can be cited.
[0099] <Thermoplastic resin composition and molded article>
[0100] The thermoplastic resin composition of the present embodiment contains the above-mentioned composite pigment and a thermoplastic resin.
[0101] Furthermore, the molded article of the present embodiment contains the above-mentioned thermoplastic resin composition.
[0102] The thermoplastic resin composition of the present embodiment contains a thermoplastic resin, and thus can be melted by heating and molded into a desired shape when a molded body is produced.
[0103] The thermoplastic resin is not particularly limited, and for example, at least one resin selected from polyethylene, ABS, polycarbonate, and the like can be used.
[0104] The amount of the thermoplastic resin in the thermoplastic resin composition is not particularly limited. For example, when the thermoplastic resin composition is used as a masterbatch (solid additive for plastics), the composite pigment is preferably 20 parts by mass or more and 200 parts by mass or less relative to 100 parts by mass of the thermoplastic resin. In the case of less than 20 parts by mass, the tinting power is weak, and the desired design may not be obtained. On the other hand, in the case of more than 200 parts by mass, it is difficult to use as a masterbatch. In the case of using the thermoplastic resin composition for the manufacture of a molded body such as injection molding, the composite pigment is preferably 0.01 parts by mass or more and 30 parts by mass or less relative to 100 parts by mass of the thermoplastic resin. In the case of less than 0.01 parts by mass, the tinting power is weak, and the desired design may not be obtained. On the other hand, in the case of more than 30 parts by mass, there is a tendency that the mechanical strength of the molded body is significantly reduced.
[0105] It should be noted that the thermoplastic resin composition is not particularly limited as long as it contains the above-mentioned composite pigment and a thermoplastic resin. For example, a composition containing a powder such as a compound or masterbatch, or a solvent for a coating, ink, cosmetic, etc. is also included in the thermoplastic resin composition.
[0106] Example
[0107] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these.
[0108] (Example 1)
[0109] [Preparation of substrate particles]
[0110] 600 mL of mineral spirits were added to a three-necked flask, and 286.0 g of aluminum flake pigment (trade name: "CS460", metal content 70% by mass, average particle size 16 μm, manufactured by Toyo Aluminum Co., Ltd.) and 40.0 g of DIACID 1550 (manufactured by Harima Chemicals Co., Ltd.) as a substrate were added thereto, and after heating and stirring at 100° C., the mixture was cooled to room temperature and degreased by filtering. Thus, degreased aluminum flakes (solid content 70% by mass) used as substrate particles were obtained.
[0111] [Pigment adhesion process]
[0112] Next, the following materials were put into a kneader and stirred at 80° C. for 1 hour.
[0113] Degreased aluminum sheet (substrate particles): 200.0 g (based on solid content)
[0114] Mineral spirit (non-polar solvent): 400mL
[0115] Blue pigment (LIONOL BLUE 7185-PM, manufactured by TOYOCOLOR CO., LTD.): 150.0 g
[0116] Aliphatic dicarboxylic acid (DIACID 1550, manufactured by Harima Chemicals Co., Ltd.): 10.0 g
[0117] Hindered amine (ADK STAB LA-67, manufactured by ADEKA Co., Ltd.): 10.0g
[0118] Thus, a slurry containing aluminum flakes (pigment-coated particles) having a pigment and a resin attached to the surface was obtained.
[0119] [Pigment layer forming process]
[0120] Next, the total amount of slurry containing the obtained pigment-coated particles was added to 1000 mL of mineral spirits in a three-necked flask, and 1.0 g of acrylic acid was further added and stirred. Furthermore, a liquid obtained by dissolving 40.0 g of trimethylolpropane trimethacrylate, 10.0 g of divinylbenzene and 5.0 g of azobisisobutyronitrile in 150 mL of mineral spirits was added to a three-necked flask, and the mixture was stirred at 100 ° C for 6 hours while blowing nitrogen. Then, the slurry cooled to room temperature was filtered to obtain particles (resin-coated particles) in which the surface of the substrate particles was coated with a resin having a cross-linked structure of trimethylolpropane trimethacrylate and divinylbenzene.
[0121] The amount of the resin (trimethylolpropane trimethacrylate and divinylbenzene) used here was 29.4% by mass based on the total amount of the pigment and the binder.
[0122] (Metal oxide adhesion: silica coating)
[0123] The obtained resin-coated particles (solid content 100 g, metal content 47.6 g) were dispersed in 1000 mL of isopropyl alcohol (IPA) in a three-necked flask to prepare a slurry, and the slurry was heated to 50° C. 30 g of water was added to the heated slurry, and an appropriate amount of monoethanolamine was added to adjust the pH of the slurry to 8.5.
[0124] Next, 30 g of tetraethoxysilane (hereinafter abbreviated as "TEOS") as a metal compound (raw material of metal oxide) (solid content after reaction is 8.4 g, 16.0 mass % (in terms of solid content) relative to the total amount of pigment and binder) is slowly added to the slurry, and further stirred and mixed at 70°C for 6 hours, thereby causing TEOS to precipitate in the form of silica on the surface of the resin matrix of the resin-coated particles. During this period, the pH value of the slurry is checked every 2 hours, and an appropriate amount of monoethanolamine is added to adjust the pH of the slurry to 8.5. After the reaction is completed, the slurry is cooled to room temperature and filtered to obtain a composite pigment having a pigment layer containing a pigment, a resin and silica (metal oxide) on the surface (refer to Figure 2 ).
[0125] (Example 2)
[0126] A composite pigment was obtained in the same manner as in Example 1 except that the amount of TEOS was changed to 7 g (3.7% by mass relative to the total amount of the pigment and the binder) in the metal oxide adhesion step.
[0127] (Example 3)
[0128] A composite pigment was obtained in the same manner as in Example 1 except that the amount of TEOS was changed to 15 g (8.0% by mass relative to the total amount of the pigment and the binder) in the metal oxide adhesion step.
[0129] (Comparative Example 1)
[0130] A composite pigment of Comparative Example 1 in which a layer containing only the pigment and the resin was formed on the surface of the substrate particles was obtained in the same manner as in Example 1 except that the metal oxide attaching step was omitted.
[0131] (Comparative Example 2)
[0132] In the resin coating step, the resin material used was changed to 1.0 g of acrylic acid, 120.0 g of trimethylolpropane trimethacrylate, 30 g of divinylbenzene, and 5.0 g of azobisisobutyronitrile. A composite pigment of Comparative Example 2 was obtained in the same manner as in Example 1 except for the above.
[0133] It should be noted that in the obtained composite pigment of Comparative Example 2, a layer of a composite body including a pigment, a resin and a metal oxide was not formed, and a layer including a resin pigment and a resin existed separately from a layer of a metal oxide. This is considered to be because if the amount of trimethylolpropane trimethacrylate (a monomer having a polymerizable double bond) is too large, a porous resin matrix is not formed, and the metal oxide cannot penetrate into the resin matrix.
[0134] (Comparative Example 3)
[0135] In the resin coating step of Example 1, 8.4 g (solid content equivalent to 30 g of TEOS) of hydrophobic fumed silica (AEROSIL (registered trademark) R972, manufactured by Nippon AEROSIL Co., Ltd.) was added to the slurry before nitrogen blowing, and then the reaction was started.
[0136] However, the reaction was stopped because the slurry thickened during the reaction. The thickening of the slurry is believed to be due to the significant increase in the number of particles in the system caused by free fumed silica, accompanied by structural viscosity.
[0137] <Test Example 1>
[0138] Weigh 10 g of each composite pigment in terms of solid content into a PP (polypropylene) cup, add 20 g of diluent (manufactured by Nippon Paint Co., Ltd., trade name: Nax Admira 500, standard diluent) to it, and stir thoroughly with a spatula. Add 110 g of CLEAR (manufactured by Nippon Paint Co., Ltd., Nax Admira 280, correction CLEAR) to it, and stir at 500 rpm for 5 minutes with a stirrer. Add 110 g of the above diluent and 10 g of Nax Multi (10:1) #20 HARDENER to it, stir thoroughly, and thus prepare a test paint.
[0139] Next, the above-mentioned test coating was applied to one surface of a steel plate to which a mid-coat had been applied [a steel plate having, in sequence, a substrate (iron), an electrodeposited layer (zinc treatment layer), a mid-coat (chipping resistance) layer, a primer layer (for base concealment and decoration), and a top coat layer (protective layer of the primer layer)] using a spray gun (manufactured by ANEST IWATA, trade name: W-101-134G) in such a way that the dry film thickness became 13 to 15 μm, and dried at 80° C. for 20 minutes.
[0140] The surface of the steel plate coated with the test paint after drying was measured using a multi-angle spectrophotometer (MA68 manufactured by X-Rite Corporation) to measure the FI (flip-flop index) value and C * The measurement results are shown in Table 1.
[0141] It should be noted that c, which is a chromaticity index, * The value is based on the chromaticity at a colorimetric angle of 15° (a * Value and b * The measured value of the value) is calculated using the following formula (1).
[0142] c * =(a*2 +b *2 ) 1 / 2 (1)
[0143] In addition, the FI value is based on the L at the measurement angles of 15°, 45° and 110°. * Value (brightness) is L * 15°, L * 110° and L * The FI value is calculated by the following formula (2) using the measured value of 45°. The larger the difference in shadow between when viewed from the front and when viewed from an angle, the more metallic feeling can be felt visually, so it is considered that the FI value has a correlation with the metallic feeling visually.
[0144] [Mathematical formula 1]
[0145]
[0146] <Test Example 2>
[0147] 25 g of the samples prepared in the above examples and comparative examples were weighed in terms of solid content, and 90 g of butyl cellosolve was added to prepare a slurry, to which 90 g of water was added, and an appropriate amount of 10% dimethylaminoethanol aqueous solution was added to adjust the pH to 10.5.
[0148] 200 g of the slurry was weighed and placed in a gas generation tester maintained at 40° C. for 96 hours. The amount of hydrogen gas generated during this time was measured. The measurement results are shown in Table 1.
[0149] [Table 1]
[0150]
[0151] According to the results of gas generation shown in Table 1, the composite pigments of Examples 1 to 3 have significantly reduced gas generation compared to Comparative Example 1. This is considered to be because the peeling of the pigment layer from the substrate surface was suppressed in Examples 1 to 3, and the gas generation caused by the degradation reaction of the substrate particles was suppressed. In contrast, for the composite pigment of Comparative Example 1, it is considered that the pigment layer peeled from the substrate surface and hydrogen gas was generated due to the degradation reaction of the substrate particles.
[0152] In addition, according to the FI and C shown in Table 1 * The results show that the composite pigments of Examples 1 to 3 (the dried product of the coating prepared using the composite pigments of the Examples) have higher FI values and C values than the composite pigment of Comparative Example 2. *The value is higher and the color tone is more excellent. This is believed to be because the pigment layer of Examples 1 to 3 is a layer obtained by polymerizing a resin formed by polymerizing a monomer and an oligomer containing one or more monomers or oligomers having two or more polymerizable double bonds and a metal oxide, so the reduction in the chroma of the dried product (molded body) of the coating and the unevenness of the color tone are suppressed. On the other hand, regarding the resin material of Comparative Example 2, it is believed that: since the resin and silica form separate layers, the pigment layer is easily peeled off, and the chroma of the dried product (molded body) of the coating is reduced.
[0153] <Test Example 3>
[0154] In terms of solid content, 100 parts by weight of a transparent ABS resin (product name "CL-430", manufactured by DENKA Corporation) was mixed with 1 part by weight of the composite pigment of each example and comparative example, and kneaded at 230°C to obtain a thermoplastic resin composition. The obtained resin composition was injection molded into a flat plate (50 mm × 80 mm × 3 mm) using an injection molding machine "FE80S12ASE" (manufactured by Nissei Plastic Industry Co., Ltd.) with the barrel temperature set to 230°C for the nozzle part, 230°C for the front part, 225°C for the middle part, 220°C for the rear part, and 60°C for the mold temperature to obtain a molded body. The FI (flip-flop index) value and C value of the obtained molded body were measured using a multi-angle spectrophotometer (manufactured by X-Rite, MA68). * Value (color).
[0155] [Table 2]
[0156]
[0157] According to the FI and C shown in Table 2 * The results show that the composite pigments of Examples 1 to 3 (the dried product of the coating prepared using the composite pigments of the Examples) have higher FI values and C values than the composite pigment of Comparative Example 2. * The value is higher and the color tone is more excellent. This is considered to be because the resin materials of Examples 1 to 3 are free radical polymers, and at least one of the monomers and oligomers has two or more polymerizable double bonds, so the reduction in chroma of the dried product (molded body) of the coating and the unevenness of the color tone are suppressed. On the other hand, it is considered that: regarding the resin material of Comparative Example 2, the amount of monomers having polymerizable double bonds is too much, so that a layer is formed in which the resin and the metal oxide are separated, and the pigment layer is easily peeled off, thereby reducing the chroma of the molded body.
[0158] Figure 3(a) is a photograph obtained by taking the surface of a molded body obtained using the composite pigment of Example 1 at a magnification of 1000 times using an optical microscope ("Digital Microscope VHX-6000", manufactured by KEYENCE Co., Ltd.). Figure 3 (b) is a photograph of the surface of a molded body obtained by using the composite pigment of Comparative Example 1. Figure 3 In (b), the white part is the part where the pigment layer is peeled off from the surface of the composite pigment. Figure 3 It can also be seen from the photographs shown in (a) and (b) that the composite pigment of Example 1 containing silica (metal oxide) in the pigment layer (between pigments) has more suppressed peeling of the pigment from the surface of the substrate particles (aluminum flakes) than the composite pigment of Comparative Example 1 not containing metal oxide in the pigment layer.
[0159] <TEM image>
[0160] The TEM (transmission electron microscope) image of Example 1 is shown in Figures 5 to 10 , Fig.14 and Fig.15 In each figure, (a) is a BF-STEM image, and (b) is a HAADF-STEM image.
[0161] In addition, a STEM-EDX (scanning transmission electron microscope-energy dispersive X-ray analysis) image obtained by photographing Example 1 is shown in Figure 11 to Figure 13 and Fig.16 .
[0162] It should be noted that Figure 5 (a) is a BF-STEM (bright field scanning transmission electron microscope) image showing a cross section near the surface of the composite pigment of the embodiment. (b) is a HAADF-STEM (high angle annular dark field scanning transmission electron microscope) image showing a cross section near the surface of the composite pigment of the same embodiment. It should be noted that in the shooting of the FIB-STEM (focused ion beam machining-scanning transmission electron microscope) images (BF-STEM and HAADF-STEM), the acceleration voltage was 200 kV.
[0163] Figure 6 yes Figure 5 A local magnified image of the area (I). Figure 6 In the figure, the portion described as "aluminum flakes" is aluminum flakes (substrate particles).
[0164] Figure 7 yes Figure 6 A local magnified image of area (II). Figure 8 yes Figure 7A local magnified image of .
[0165] Fig. 9 yes Figure 6 A local magnified image of area (III). Fig.10 yes Fig. 9 A local magnified image of .
[0166] Fig.11 (a) is Figure 7 (b) HAADF-STEM image of almost the same field of view. Fig.11 (b)~(h) are related to Figure 7 STEM-EDX images of almost the same field of view. Figure 11 to Figure 13 and Fig.16 Among them, (b) to (h) are images showing the distribution of C, N, O, Al, Si, Cl and Cu, respectively, and the white parts in the figures are the areas where the respective elements exist.
[0167] Fig.12 (a) is Figure 8 (b) Same image. Fig.12 (b)~(h) are related to Figure 8 STEM-EDX image of the same field of view.
[0168] Fig.13 (a) is Fig.10 (b) Same image. Fig.13 (b)~(h) are related to Fig.10 STEM-EDX image of the same field of view.
[0169] Fig.14 yes Figure 6 A local magnified image of area (IV).
[0170] Fig.15 yes Fig.14 A local magnified image of .
[0171] Fig.16 (a) is Fig.15 (b) Same image. Fig.16 (b)~(h) are related to Fig.15 STEM-EDX image of the same field of view.
[0172] according to Figures 5 to 16 (Especially the distribution of Si, Cu and Cl elements Figure 11 to Figure 13 and Fig.16 ) It can be seen that in the composite pigment of the example, silicon dioxide (metal oxide) exists in a uniformly dispersed state in the pigment layer adjacent to the substrate particles (aluminum flakes).
[0173] <Specific surface area: SSA>
[0174] The results of measuring the specific surface area (SSA) of the composite pigments of Example 1 and Comparative Example 1 are shown in Table 2. For reference, the results of measuring the SSA of the aluminum pigment (CS460) before the pigment is attached are also shown in Table 2. Here, the specific surface area (SSA) was measured using Macsorb (registered trademark) HMmodel-1200 (manufactured by MOUNTECH Co., Ltd.).
[0175] [Table 3]
[0176] Aluminum Type <![CDATA[Specific surface area (m 2 / g)]]> CS460 3 Comparative Example 1 25 Example 1 70
[0177] The results shown in Table 3 show that the composite pigment of Example 1 has a larger specific surface area than that of Comparative Example 1, and forms a porous resin matrix. It should be noted that the smaller specific surface area of Comparative Example 1 than that of Example 1 is believed to be due to the absence of amorphous silica contained in the pigment layer.
[0178] The embodiments and examples disclosed this time are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the above description, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0179] Description of Reference Numerals
[0180] 1 composite pigment, 2 substrate particles, 3 pigment layer, 3a pigment, 3b resin, 3c surface (metal oxide).
Claims
1. A composite pigment comprising a substrate particle and a pigment layer provided on the surface of the substrate particle, The pigment layer contains pigment, resin and metal oxide. The pigment layer is composed of a plurality of particles in which the pigment is coated with the resin, and the metal oxide is attached to the surfaces of the plurality of particles. The resin is a free radical polymer of at least one of a monomer and an oligomer, and at least one of the monomer and the oligomer has two or more polymerizable double bonds. The metal oxide includes at least one selected from silicon oxide, polysiloxane, and a composite thereof.
2. The composite pigment according to claim 1, wherein The substrate particles contain at least one selected from the group consisting of aluminum, aluminum alloy, glass, alumina, and mica.
3. The composite pigment according to claim 1, wherein The pigment layer is porous.
4. The composite pigment according to claim 3, wherein The specific surface area of the pigment layer is 10 m 2 / g~100m 2 / g. A thermoplastic resin composition comprising the composite pigment according to claim 1. A molded body comprising the thermoplastic resin composition according to claim 5.
Citation Information
Patent Citations
Metallic color pigment and colored article
WO2014050893A1
Coated metal pigment, method for production of the pigment, and coating composition comprising the pigment
CN101287804A
Surface-coated metallic pigment, water-based coating comprising same and article coated therewith
CN102449075A